Suboptimal Health, Dietary Supplementation, and Public Health Approaches to Regulatory Challenges in Dubai - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Faris El-Dahiyat; Mohamed Azmi Hassali; Moyad Shahwan; Mina Rabea Al Ani; Hussein Ali Jabbar (SAGE Publishing, 2020)
Objectives: Presently, limited data are available on dietary supplements (DSs) and their associated effects on health status although the consumption of DS continues to expand. This study is aimed to explore the possible relationship between DSs consumption and suboptimal health status (SHS) in Dubai, United Arab Emirates (UAE). Methods: This study was a cross-sectional research held among a sample of citizens and residents in the Emirate of Dubai in the UAE using a well-structured, self-administered, anonymous survey. Frequency tables, odds ratios, and confidence intervals were generated during the data analysis using SPSS version 23. Results: A total of 618 participants were enrolled in this study and fully completed the questionnaire. In this study, 317 participants (51.3%) (95% CI: 47.3%-55.3%) reported the use of DS products. A significant association between DS consumption and suboptimal health status was detected ( P < .001). DS consumers had a 1.5-fold increased odds of suboptimal health status when compared with non-DS consumers (95% CI 1.4-1.7). Conclusion: The findings of this study suggest a need to develop policies and programs that will help minimize the risk of possible adverse events that are associated with the utilization of DSs.